Dynamic Distributed Brillouin Optical Fiber Sensing Based on Dual-Modulation by Combining Single Frequency Modulation and Frequency-Agility Modulation - Dexin Ba; Dengwang Zhou; Benzhang Wang; Zhiwei Lu; Zhigang Fan; Yongkang Dong; Hui Li (IEEE Photonics Journal, 2017)
Dynamic Brillouin optical fiber sensors based on fast scanning of Brillouin gain spectrum (BGS) are one of the most promising techniques to measure dynamic strains, where an ∼11-GHz bandwidth arbitrary waveform generator (AWG) or a vector microwave generator is essential for frequency agility. A dynamic Brillouin optical fiber sensor based on dual-modulation is proposed here, which aims to realize dynamic sensing via a low-bandwidth AWG. In this protocol, the scanning of BGS is implemented by the combination of a single-frequency modulation and a frequency-agility modulation. The frequency of the single-frequency modulation is slightly lower than the Brillouin frequency shift of the fiber under test so that the tuning range of the frequency-agility modulation is required to cover only several-hundred MHz for the scanning of the BGS, which significantly reduces the bandwidth requirement for the AWG. In experiment, an 11.8-Hz strain is measured with a 30-m fiber, where the spatial resolution and the sampling rate are 1 m and 200 Hz, respectively. Furthermore, by tracking the damping vibration of the optical fiber, its resonant frequency is measured with a sampling rate of 100 Hz.